Study of The Effect of Temperature On The Desorption Efficiency of Precious Metals In The Elution Process Using Anglo American Research Laboratories (AARL) Method - Frideni Yushandiana Putri G.F.; Mei Iftita Mawarda'; Sulaeman - -; Riria Zendy Mirahati; Shofa Rijalul Haq (Program studi Teknik Kimia UNS, 2024)
The elution process, known as the desorption of gold from carbon into solution, uses high temperature and pressure. Activated carbon is used as an adsorbent in the precious metal adsorption process. PT Indo Muro Kencana uses the Anglo American Research Laboratories (AARL) method to desorb valuable metals from the activated carbon of the Carbon In Pulp (CIP) process. The elution process of this research involves 9 stages: Pre-heat, Pre-soak 1, Pre-soak Circulation, Lean 1, Presoak 2, Lean 2, Water Elution 1, Water Elution 2, and Cooling. This study found that copper (Cu) metal desorbed from carbon first, followed by silver (Ag) metal, with the desorption of gold (Au) metal occurring last due to the influence of the stability value of metal cyanide complexes. High cyanide concentrations ( 10% CN-) were given in Pre-soak 1, Pre-soak Circulation, and Pre-soak 2. The elution process is significantly affected by high process temperatures, particularly 123°C in the Lean 2 stage, which effectively desorbs gold (Au) at its optimal point. The solution product that only contains copper from the initial 60 minutes of the Pre-heat and Pre-soak 1 processes was transferred to the tailings tank to improve the efficiency of the refining process. The total recoveries for gold (Au), silver (Ag), and copper (Cu) were 93.1%, 95%, and 94.7%, respectively.